PERTANGGUNGJAWABAN PIDANA PEREDARAN NARKOTIKA TERHADAP ANAK DIBAWAH UMUR DI WILAYAH HUKUM KEPOLISIAN RESOR KLUNGKUNG - Satriana, I Made Wahyu Chandra; Dewi, Ni Made Liana; Satriawan, Km Edy (Kerta Dyatmika, 2024)
Legal protection for children is a responsibility of the state as mandated in Article 1 point 1 of the Child Protection Act, which defines a child as any person under the age of 18, including those still in the womb. In the era of globalization, there has been a growing involvement of children in criminal acts, notably in the distribution of narcotics. This study aims to analyze the criminal liability imposed on children involved in narcotics distribution within the jurisdiction of Klungkung Police Department, as well as to identify the efforts made by law enforcement in addressing such offenses. The research employs an empirical legal research method, grounded in the principles of legality, legal certainty, juvenile delinquency, and criminal liability. The data utilized comprises both primary and secondary sources collected through interviews and document studies. These data are then analyzed using qualitative methods combined with deductive legal reasoning and presented in a descriptive-qualitative and systematic manner. The findings indicate that the criminal liability for child offenders involved in narcotics distribution may be addressed through diversion mechanisms, treatment, rehabilitation, and sentencing. Furthermore, the Klungkung Police Department undertakes both preventive (pre-emptive) and repressive (enforcement) measures to combat narcotics offenses involving minors. In conclusion, the legal approach to child narcotics offenders in the jurisdiction of the Klungkung Police emphasizes restorative justice principles through diversion, combined with rehabilitative actions aimed at safeguarding the child’s future development.